HOW COVID 19 AFFECT SOCIOEMOTIONAL WEALTH DIMENSIONS? - Agustiono Agustiono (Proceeding of the International Conference on Family Business and Entrepreneurship, 2021)
This research aim at assessing the impact of Covid 19 crisis toward family business’ Socioemotional Wealth’s (SEW) dimensions. SEW framework differentiate the unique entity of family business to non family business.  It identifies why family business decision making do not merely based on financial consideration but also family’s welfare and emotional attachment. Five SEW dimensions that will be explore are known as FIBER (Family control, Identification, Binding social Ties, Emotional attachment and Renewal of the family bond). As Indonesia enter a recession as shown by a decrease in GDP quarterly data 2020, it will put a strain on the family business decision as most business now fall into surviving mode. The question will be weather the pressure of survivability reduce the intensity of SEW in family business or, on the contrary, the pressure will change the degree of SEW dimensions? The method used to answer this will be an explanatory single case study. The exploitative study showed that other than financial preparedness, respectable approach to family members, shareholders and stakeholders prior crisis are an important factors in determining changes of SEW degree during crisis.   Keywords: Family business, Socioemotional Wealth, Crisis